Conductive composition and composite using the same
A conductive composition of electrolytic silver powder and addition-curing silicone rubber addresses the challenge of maintaining conductivity and stretchability in biomimetic drive materials by balancing volume ratios and densities, achieving a film with low resistivity and high elasticity.
Patent Information
- Application Number
- JP2024173958
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-03
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing conductive films used in biomimetic drive materials face challenges in maintaining conductivity and stretchability when stretched to twice their length, and platinum-based catalysts inhibit curing of materials like silver powder, making film formation difficult.
A conductive composition containing electrolytic silver powder and addition-curing silicone rubber, with a specific volume ratio and tap density, is used to form a conductive film that balances electrical conductivity and elasticity, using an organic solvent to improve handleability and workability.
The composition achieves a conductive film with excellent conductivity and stretchability, maintaining low volume resistivity even after stretching to twice its length, suitable for applications in biomimetic drive materials.
Smart Images

Figure 2024177362000007 
Figure 2024177362000001 
Figure 2024177362000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrically conductive composition and a composite using the same. [Background technology]
[0002] In recent years, efficiency improvements have been made in fields such as manufacturing and nursing care through automation and mechanization of work. Accordingly, research into robots and wearable power assist devices has accelerated. Biomimetic driving materials such as artificial muscles and actuators used in this type of application require wiring and conductive circuits (conductive films) to be formed on a stretchable substrate using conductive compositions in order to send electrical signals for driving. The conductive film must be stretchable enough to maintain conductivity even when the biomimetic driving material is repeatedly stretched and contracted.
[0003] Patent Documents 1 to 3 are examples of prior art documents related to stretchable conductive films. For example, Patent Document 1 discloses a conductive paste that contains an elastomer, a conductive filler, and a solvent and is used to form wiring that constitutes a stretchable wiring board. Patent Document 1 describes that the conductivity of the wiring can be maintained even after the stretchable wiring board is repeatedly stretched by 20% in the length direction. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-110093 A [Patent Document 2] International Publication No. 2017 / 217509 [Patent Document 3] International Publication No. 2017 / 026420 Summary of the Invention [Problem to be solved by the invention]
[0005] However, biomimetic actuator materials may require higher levels of stretchability, such as a conductive film that can maintain its conductivity even when stretched to twice its original length (200%) and then returned to its original length (100%), and preferably with only a small increase in resistance after stretching.
[0006] Also, for example, when the conductive paste used to form the conductive film contains an elastomer, silicone rubber or the like is used as the elastomer. Among silicone rubbers, addition-curing silicone rubber, which is cured by heat treatment at a relatively low temperature (for example, 100°C or less), is preferably used from the viewpoint of suppressing damage to the biomimetic actuator material by heat. However, on the other hand, a platinum-based catalyst is required for curing the addition-curing silicone rubber, and the platinum-based catalyst causes curing inhibition for various materials, which is an issue. In particular, when silver powder synthesized by a liquid phase method is used as the conductive filler, it is known that the curing inhibition by the platinum-based catalyst occurs significantly, making it difficult to cure the film.
[0007] The present invention has been made in consideration of the above circumstances, and a main object of the present invention is to provide a conductive composition that contains an addition-curing type silicone rubber and silver powder and is capable of forming a conductive film with improved elasticity. [Means for solving the problem]
[0008] In order to achieve the above object, the present invention provides a conductive composition comprising electrolytic silver powder and an addition-curing silicone rubber. The conductive composition disclosed herein has a tap density (g / cm 3 ) is the true density (g / cm 3 ) and multiplying the result by 100 is taken as X (volume %), and the ratio of the volume of the electrolytic silver powder to the total volume of the electrolytic silver powder and the silicone rubber is taken as Y (volume %), and the following formula is obtained: 1.5≦(Y / X)≦4.0 The present invention is characterized in that:
[0009] As described above, the conductive composition disclosed herein is characterized in that it contains electrolytic silver powder as silver powder. Generally, silver powder synthesized by a liquid phase method or the like is used, but such silver powder may have amine components derived from synthetic reagents attached thereto. When such silver powder is used in combination with an addition-curing silicone rubber, there is a problem that the platinum-based catalyst added is poisoned by the amine components, etc., resulting in insufficient progress of film curing. In contrast, when electrolytic silver powder obtained by electrolytically refining metallic crude silver in an electrolyte solution is used, curing inhibition by the platinum-based catalyst can be suppressed, which is preferable. Furthermore, when the ratio (Y / X) satisfies the above-mentioned range, a conductive film having both electrical conductivity and excellent elasticity can be formed.
[0010] In a preferred embodiment disclosed herein, the volume ratio (Y) of the electrolytic silver powder is 10% by volume or more and 40% by volume or less, which allows the conductive film to have a good balance between electrical conductivity and elasticity.
[0011] In a preferred embodiment disclosed herein, the electrolytic silver powder has a tap density of 1.5 g / cm 3 This allows the silicone rubber to easily enter the gaps in the electrolytic silver powder, making it possible to more suitably improve the elasticity of the conductive film.
[0012] In a preferred embodiment disclosed herein, the packing rate (X) of the electrolytic silver powder is 5% by volume or more and 15% by volume or less. When the packing rate is a predetermined value or more, the electrolytic silver particles in the conductive film are easily in contact with each other, and the electrical conductivity of the conductive film can be more appropriately improved. When the packing rate is a predetermined value or less, the silicone rubber easily enters the pores of the electrolytic silver powder, and the elasticity of the conductive film can be more appropriately improved.
[0013] In a preferred embodiment disclosed herein, the conductive composition contains an organic solvent and is prepared in a paste form, which can improve the handleability of the conductive composition and the workability during the formation of a conductive film.
[0014] In a preferred embodiment disclosed herein, the organic solvent has a solubility parameter (SP value) of 6 (cal / cm 3 ) 0.5 More than 8(cal / cm 3 ) 0.5 The following compounds are included. This enhances compatibility with silicone rubber, making it possible to stably prepare a homogeneous paste.
[0015] The present invention also provides a composite comprising a substrate and a conductive film formed on the substrate and made of a dried product of the conductive composition according to any one of claims 1 to 6.
[0016] In a preferred embodiment disclosed herein, the conductive film has a volume resistivity of 1 Ω·cm or less, thereby making it possible to realize a conductive film with excellent electrical conductivity.
[0017] In a preferred embodiment disclosed herein, when the composite is stretched to twice its original length and then returned to its original length, the increase rate of the volume resistivity of the conductive film is 10% or less, thereby making it possible to realize a conductive film with excellent elasticity. [Brief description of the drawings]
[0018] [Figure 1] 1 is a cross-sectional view illustrating a schematic diagram of a wiring board according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] A preferred embodiment of the technology disclosed herein will be described below. Note that matters other than those specifically mentioned in this specification (e.g., the configuration of the conductive composition) and necessary for carrying out the present invention (e.g., the preparation method and the use method of the conductive composition) can be carried out based on the technical content taught by this specification and the general technical common sense of a person skilled in the art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense of the relevant field. In this specification, the expression "A to B (A and B are arbitrary values)" indicating a numerical range includes the meaning of "A or more and B or less", as well as "preferably larger than A" and "preferably smaller than B".
[0020] <Conductive composition> The conductive composition disclosed herein contains (A) electrolytic silver powder and (B) addition-curing silicone rubber as its main components. The conductive composition typically contains (C) an organic solvent and can be prepared in a paste form (including a slurry form and an ink form; the same applies below). The conductive composition can further contain (D) other optional components. The conductive composition can be prepared, for example, by dispersing or dissolving (A) electrolytic silver powder, (B) addition-curing silicone rubber, and (D) other optional components in (C) an organic solvent.
[0021] The conductive composition disclosed herein can be used to form a conductive film. In this specification, the term "conductive film" refers to a film-like body (dried product) obtained by drying the conductive composition at a temperature lower than the heat resistance temperature (i.e., the limit temperature of use) of the addition curing type silicone rubber (B), typically 200°C or less, for example 150°C or less, further 120°C or less, and preferably 100°C or less. Each of the components will be described below in order.
[0022] <(A) Electrolytic silver powder> The conductive composition disclosed herein includes electrolytic silver powder. In this specification, "electrolytic silver powder" refers to silver powder obtained by, for example, electrolytic refining of crude silver metal in an electrolyte solution (i.e., electrolytic method). Unlike silver powder obtained by a liquid phase method, etc., the silver powder obtained by the electrolytic method is less likely to contain substances that poison platinum catalysts, such as amine components, and therefore can be preferably used in the technology disclosed herein.
[0023] The properties of the particles constituting the electrolytic silver powder (hereinafter also referred to as "electrolytic silver particles"), such as size and shape, are not particularly limited as long as they satisfy the ratio (Y / X) described later. The size of the electrolytic silver particles can be appropriately selected, for example, according to the use of the conductive composition and the dimensions of the conductive film to be formed. In addition, the size of the electrolytic silver particles may be selected so as to fit within the minimum dimensions of the conductive film, such as the thickness and / or width. Although not particularly limited, the average particle size (D50) of the electrolytic silver particles may be approximately 0.1 μm or more, preferably 0.5 μm or more, for example, 1 μm or more, 2 μm or more, 3 μm or more, or 5 μm or more. When the average particle size is a predetermined value or more, (B) the addition curing type silicone rubber is easily inserted into the gaps of the electrolytic silver powder. This increases the adhesion between the electrolytic silver powder and the addition curing type silicone rubber, and the elasticity of the conductive film can be more suitably improved. The average particle size (D50) of the electrolytic silver particles may be approximately 50 μm or less, for example, 30 μm or less, 20 μm or less, or 10 μm or less. When the average particle size is a predetermined value or less, the electrolytic silver particles are easily in contact with each other, and the electrical conductivity of the conductive film can be more suitably improved.
[0024] In this specification, the term "average particle size (D50)" refers to the particle size (50% volume average particle size) that corresponds to 50% cumulatively from the fine particle side in the volume-based particle size distribution measured by a laser diffraction / light scattering method.
[0025] The shape of the electrolytic silver particles may be, for example, dendritic (dendrite-like), acicular (including spindle-like and cylindrical), scaly (flake-like), roughly spherical, irregular, etc. Although not particularly limited, the electrolytic silver particles may be in a shape such that the average aspect ratio (major axis / minor axis ratio) is 2 or more, further 3 or more, for example, dendritic or acicular. This allows the conductive network to be suitably formed in the direction of expansion and contraction of the conductive film, thereby improving electrical conductivity. Among them, dendritic shapes are preferred.
[0026] In this specification, the term "aspect ratio" refers to the ratio (b / a) of the length (b) of the long side of a particle to the length (a) of the short side of a particle when a rectangle is drawn circumscribing the image of an electrolytic silver particle observed under an electron microscope. The average aspect ratio refers to the arithmetic average value of the aspect ratios of multiple particles (e.g., 100 particles). In addition, in this specification, the term "dendritic" refers to a shape in which multiple branches extend two-dimensionally or three-dimensionally from the longest main axis when an electrolytic silver particle is observed under an electron microscope.
[0027] The electrolytic silver particles may be in the form of an agglomerated powder in which a plurality of electrolytic silver particles (primary particles) are agglomerated three-dimensionally. The primary particles may be approximately spherical or irregular in shape. In the agglomerated powder, the primary particles are in physical contact with each other, so that a conductive network is preferably formed in the direction of expansion and contraction of the conductive film, and electrical conductivity can be improved. In addition, the agglomerated powder or dendritic electrolytic silver particles are relatively bulky and have a small tap density compared to, for example, approximately spherical electrolytic silver particles, so that (B) the addition-curing silicone rubber can easily enter the gaps between the electrolytic silver powder. This increases the adhesion between the electrolytic silver powder and the addition-curing silicone rubber, and can more preferably improve the expansion and contraction of the conductive film.
[0028] Although not particularly limited, the tap density of the electrolytic silver powder is preferably 1.5 g / cm 3 Less than or equal to 1.4 g / cm 3 More preferably, 1.35 g / cm 3 For example, 1.0 g / cm 3 ~1.35g / cm3 When the tap density is equal to or less than a predetermined value, the (B) addition-curing silicone rubber is easily inserted into the gaps in the electrolytic silver powder. This increases the adhesion between the electrolytic silver powder and the addition-curing silicone rubber, and the elasticity of the conductive film can be more suitably improved. The tap density of the electrolytic silver powder is approximately 0.1 g / cm 3 More than 0.2 g / cm, preferably 0.2 g / cm 3 More preferably, 0.5 g / cm 3 or more, for example 0.5 g / cm 3 ~1.0g / cm 3 , 0.6g / cm 3 ~0.7g / cm 3 When the tap density is a predetermined value or more, the electrolytic silver powder particles are easily contacted with each other, and the electrical conductivity of the conductive film can be more suitably improved. The tap density of the electrolytic silver powder can be adjusted, for example, by pulverizing or classifying the electrolytic silver powder.
[0029] In this specification, the term "tap density" refers to the apparent density (bulk density) after electrolytic silver powder is put into a specified container, tapped 1000 times, and subjected to a compressive force due to inertia. The tap density can be measured in accordance with "Metal powder - Tap density measurement method" specified in JIS Z2512:2012.
[0030] Although not particularly limited, the packing rate X of the electrolytic silver powder, which is represented by the following formula: (tap density / true density) × 100, can be generally 3 vol% or more, preferably 4 vol% or more, 5 vol% or more, or 5.5 vol% or more. The true density means the value obtained by dividing the mass of the electrolytic silver powder by the volume of the electrolytic silver powder itself, excluding the inside of the electrolytic silver particles and the voids between the electrolytic silver particles. The true density of silver is 10.5 g / cm 3As described above, the tap density refers to the bulk density after the application of a compressive force due to inertia. Therefore, the larger the value of the filling rate X, the fewer the voids. When the filling rate X is a predetermined value or more, the electrolytic silver particles in the conductive film are more likely to come into contact with each other, and the electrical conductivity of the conductive film can be more suitably improved. The filling rate X can be approximately 30% by volume or less, preferably 20% by volume or less, 15% by volume or less, or 13% by volume or less. When the filling rate X is a predetermined value or less, the (B) addition-curing silicone rubber is more likely to enter the voids of the electrolytic silver powder. This increases the adhesion between the electrolytic silver powder and the addition-curing silicone rubber, and the elasticity of the conductive film can be more suitably improved.
[0031] Although not particularly limited, when the total volume of the (A) electrolytic silver powder and the (B) addition curing type silicone rubber is taken as 100 volume%, the volume ratio Y of the electrolytic silver powder can be approximately 5 volume% or more, preferably 10 volume% or more, 12 volume% or more. When the volume ratio is a predetermined value or more, the electrolytic silver particles in the conductive film are easily contacted with each other, and the electrical conductivity of the conductive film can be more suitably improved. The volume ratio Y is typically smaller than that of the (B) addition curing type silicone rubber, and can be approximately less than 50 volume%, preferably 45 volume% or less, 40 volume% or less, 36 volume% or less. When the volume ratio is a predetermined value or less, the (B) addition curing type silicone rubber is easily inserted into the gaps of the electrolytic silver powder. This increases the adhesion between the electrolytic silver powder and the addition curing type silicone rubber, and the elasticity of the conductive film can be more suitably improved. The volume of the electrolytic silver powder can be calculated by dividing the mass of the electrolytic silver powder by its true density, and the volume of the addition-curing silicone rubber can be calculated by dividing the mass of the addition-curing silicone rubber by its density.
[0032] In this embodiment, the above-mentioned filling rate X and the above-mentioned volume ratio Y of the electrolytic silver powder satisfy the following formula: 1.5≦(Y / X)≦4.0. By setting the above-mentioned ratio (Y / X) to a predetermined value or less, it is possible to impart excellent elasticity to the conductive film. Furthermore, by setting the above-mentioned ratio (Y / X) to a predetermined value or more, it is possible to impart electrical conductivity to the conductive film. From the viewpoint of improving the electrical conductivity of the conductive film, the above-mentioned ratio (Y / X) can be preferably set to 1.7 or more, 2.0 or more, or 2.1 or more. Furthermore, the above-mentioned ratio (Y / X) can be preferably set to 3.8 or less, 3.0 or less, or 2.8 or less. The above-mentioned ratio (Y / X) can be set to, for example, 1.7 to 3.8.
[0033] <(B) Addition-curing silicone rubber> The conductive composition disclosed herein includes an addition-curing type silicone rubber. Silicone rubber is a component that imparts flexibility and elasticity to the conductive film, and is an organic compound containing silicon (Si). The addition-curing type silicone rubber may be a heat-addition-curing type silicone rubber in which a curing reaction proceeds by heating, or a room-temperature addition-curing type silicone rubber in which a curing reaction proceeds at room temperature (e.g., 20±5°C). The addition-curing type silicone rubber may be a liquid silicone rubber that has fluidity under conditions of room temperature (e.g., 20±5°C) and normal pressure.
[0034] The addition curing silicone rubber is not particularly limited, and among conventionally known silicone rubbers, one type may be used alone or two or more types may be used in appropriate combination depending on, for example, the application of the conductive composition. The addition curing silicone rubber may be, for example, an organopolysiloxane having at least one alkenyl group bonded to a silicon atom in the molecule represented by the following average composition formula (I). R a SiO (4-a) / 2 (I) Here, R in the above formula (I) represents the same or different unsubstituted or substituted monovalent hydrocarbon group, and may be, for example, a hydrocarbon group having 1 to 20 carbon atoms, or even 1 to 10 carbon atoms. Specific examples include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and octyl groups, cycloalkyl groups such as cyclopentyl and cyclohexyl groups, alkenyl groups such as vinyl, allyl, and propenyl groups, aryl groups such as cycloalkenyl groups, phenyl and tolyl groups, and aralkyl groups such as benzyl and 2-phenylethyl groups. Alternatively, examples include groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine, chlorine, and bromine atoms, or cyano groups. Among these, methyl, vinyl, phenyl, and trifluoropropyl groups are preferred, and methyl and vinyl groups are particularly preferred. In addition, a in the above formula (I) may be a positive number of 1.95 to 2.05.
[0035] Addition-curing silicone rubber is, for example, a diorganosiloxane unit (RSiO 2 / 2 Preferably, the repeating structure of the above (R is the same as above, hereinafter) is composed of only dimethylsiloxane units. Also preferably, diorganosiloxane units such as methylvinylsiloxane units, methylphenylsiloxane units, diphenylsiloxane units, and methyl-3,3,3-trifluoropropylsiloxane units are introduced into a dimethylpolysiloxane structure composed of the repeating dimethylsiloxane units constituting the main chain.
[0036] Both ends of the molecular chain may be, for example, triorganosiloxy groups (RSiO 1 / 2 ) and the like. In addition, hydroxydiorganosiloxy groups such as hydroxydimethylsiloxy groups (R2(HO)SiO 1 / 2 ) or the like.
[0037] The density of addition curing silicone rubber is approximately 0.5 to 2 g / cm 3 , preferably 1.0±0.3g / cm 3 , e.g. 1.0±0.2g / cm 3 This allows the effect of the technology disclosed herein to be achieved at a higher level. The density of addition-curing silicone rubber is a value specific to the substance, and values described in, for example, various conventionally known documents, dictionaries, manufacturer product catalogs, etc., can be used. In addition, it can also be measured by, for example, the liquid phase displacement method (pycnometer method) in accordance with JIS K0061: "Method for measuring density and specific gravity of chemical products" specified in 2001.
[0038] Although not particularly limited, the hardness of the addition curing silicone rubber is generally 35 degrees or less, preferably 30 degrees or less. By setting the hardness to a predetermined value or less, the flexibility of the conductive film can be increased, and the elasticity of the conductive film can be more suitably improved. In this specification, the "hardness of the addition curing silicone rubber" refers to the hardness measured using a type A durometer (rubber hardness tester). The hardness of the addition curing silicone rubber can be measured in accordance with JIS K6253-3: "Vulcanized rubber and thermoplastic rubber - Determination of hardness - Part 3: Durometer hardness" specified in 2012.
[0039] Although not particularly limited, the elongation at break of the addition curing silicone rubber is generally 200% or more, preferably 250% or more, for example 300% or more. By making the elongation at break a predetermined value or more, the flexibility of the conductive film can be increased, and the elasticity of the conductive film can be more suitably improved. In this specification, the "elongation at break of the addition curing silicone rubber" refers to the elongation when a predetermined test piece is prepared, pulled by a tensile tester, and the test piece is broken. The elongation at break is expressed as a ratio (%) to the initial length of the test piece. That is, it is expressed by the following formula: {(length at break of the test piece L1-initial length of the test piece L0) / initial length of the test piece L0}×100(%);. The elongation at break of the addition curing silicone rubber can be measured in accordance with "Vulcanized rubber and thermoplastic rubber-Determination of tensile properties" specified in JIS K6251:2010.
[0040] The conductive composition may be mainly composed of addition-curing silicone rubber (a component that accounts for 50% by volume or more) on a volume basis. Although not particularly limited, when the total volume of the (A) electrolytic silver powder and the (B) addition-curing silicone rubber is taken as 100% by volume, the volume ratio of the addition-curing silicone rubber is typically larger than that of the (A) electrolytic silver powder, and may be approximately 50% by volume or more, preferably 60% by volume or more, 65% by volume or more, for example 70% by volume or more. When the volume ratio is a predetermined value or more, the elasticity of the conductive film can be more suitably improved. The volume ratio of the addition-curing silicone rubber may be approximately 95% by volume or less, preferably 90% by volume or less, for example 85% by volume or less. When the volume ratio is a predetermined value or less, the electrolytic silver particles in the conductive film are more likely to come into contact with each other, and the electrical conductivity of the conductive film can be more suitably improved.
[0041] Although not particularly limited, when the entire conductive composition is taken as 100 mass%, the mass ratio of the addition curing type silicone rubber may be approximately 5 mass% or more, typically 7 mass% or more, for example 10 mass% or more, 15 mass% or more. When the mass ratio is a predetermined value or more, the elasticity of the conductive film can be more suitably improved. The mass ratio of the silicone rubber may be approximately 50 mass% or less, typically 40 mass% or less, 35 mass% or less, for example 30 mass% or less. When the mass ratio is a predetermined value or less, electrolytic silver particles in the conductive film are more likely to come into contact with each other, and the electrical conductivity of the conductive film can be more suitably improved.
[0042] In addition, a curing agent (catalyst, crosslinking agent, etc.) may be used in the curing reaction of the addition curing type silicone rubber. As the catalyst, a catalyst that is conventionally known as a catalyst for addition reaction curing type silicone rubber compositions can be used. As such a catalyst, for example, a platinum group metal catalyst (metallic platinum group metals and their compounds, etc.) can be mentioned. In addition, the amount of catalyst added can be within a range that can contribute to the promotion of the addition reaction (for example, a catalytic amount). The crosslinking agent may be any of those known in the art for use as crosslinking agents for addition reaction curing silicone rubber compositions. Examples of such crosslinking agents include organohydrogenpolysiloxanes (1,1,3,3-tetramethyldisiloxane, methylhydrogencyclopolysiloxane, methylhydrogenpolysiloxanes capped with trimethylsiloxy groups at both ends, dimethylpolysiloxanes capped with dimethylhydrogensiloxy groups at both ends, etc.). The amount of the crosslinking agent added is not limited thereto, but may be, for example, 0.1 to 30 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.3 to 10 parts by mass relative to 100 parts by mass of the organopolysiloxane.
[0043] In addition to the above catalysts, an addition crosslinking regulator may be used to adjust the curing rate, such as ethynylcyclohexanol or tetramethyltetravinylcyclotetrasiloxane.
[0044] <(C) Organic solvent> The organic solvent is an optional component that dissolves or disperses the solid components of the conductive composition, mainly (A) the electrolytic silver powder and (B) the addition-curing silicone rubber, to adjust the fluidity of the conductive composition. By adjusting the fluidity of the conductive composition, the handleability of the conductive composition and the workability during the formation of a conductive film can be improved.
[0045] The organic solvent is not particularly limited, and one type alone or two or more types in appropriate combination can be used among conventionally known ones depending on, for example, the use of the conductive composition and the type of substrate on which the conductive film is formed. Examples of the organic solvent include hydrocarbon solvents, ether solvents, ester solvents, glycol solvents, glycol ether solvents, glycol ester solvents, and alcohol solvents. Examples of the hydrocarbon solvent include aliphatic hydrocarbons such as N-pentane, N-hexane, cyclohexane, N-heptane, N-nonane, N-octane, N-decane, N-undecane, N-dodecane, tridecane, tetradecane, kerosene, petroleum hydrocarbons, naphtha, dipentene, and turpentine oil, and aromatic hydrocarbons such as benzene, toluene, and xylene. The organic solvent may be a non-polar solvent. Among them, from the viewpoint of improving the storage stability of the conductive composition and the handling during the formation of the conductive film, those that are difficult to volatilize and have low flammability (for example, a flash point of 40° C. or higher) are preferable.
[0046] Although not particularly limited, the solubility parameter (SP value) of the organic solvent is generally 4 (cal / cm 3 ) 0.5 Above 5 (cal / cm 3 ) 0.5 More than 6 (cal / cm 3 ) 0.5 For example, 6.5 (cal / cm 3 ) 0.5 The solubility parameter of the organic solvent is generally 10 (cal / cm 3 ) 0.5 Below 9 (cal / cm 3 ) 0.5 Less than 8 (cal / cm3 ) 0.5 or less. The SP value is a value that is a measure of the "ease of mixing" between the solid content of the conductive composition and the organic solvent. According to the study by the present inventors, by setting the solubility parameter of the organic solvent in the above range, it is possible to increase the compatibility with the (B) addition-curing type silicone rubber, and to stably prepare a homogeneous paste. In addition, it is possible to expand the range (variation) of applicable substrates.
[0047] In this specification, the term "solubility parameter (SP)" refers to the solubility parameter calculated by the so-called Fedors method described in RF Fedors, Polymer Engineering Science, 14, p. 147 (1974). The solubility parameter is a value specific to each compound. The SI unit of the SP value is (J / cm 3 ) 0.5 or (MPa) 0.5 However, in this specification, the term (cal / cm 3 ) 0.5 The unit of SP value is expressed by the following formula: 1(cal / cm 3 ) 0.5 ≒2.05(J / cm 3 ) 0.5 ≒2.05(MPa) 0.5 ; can be converted.
[0048] When the conductive composition contains an organic solvent, the amount of the organic solvent may be adjusted appropriately so that the solid content can be dissolved or dispersed homogeneously and the viscosity is suitable for forming a conductive film. As an example, when the entire conductive composition is taken as 100 mass%, the mass ratio of the organic solvent may be approximately 5 mass% or more, typically 7 mass% or more, for example 10 mass% or more, 15 mass% or more. The mass ratio of the organic solvent may be approximately 50 mass% or less, typically 40 mass% or less, 35 mass% or less, for example 30 mass% or less. By suppressing the amount of the solvent to the minimum necessary, a dense conductive film can be formed, and at least one of the electrical conductivity and elasticity of the conductive film can be more suitably improved.
[0049] <(D) Other optional ingredients> In addition to the above-mentioned components, the conductive composition may further contain various optional components as necessary, as long as the effect of the technology disclosed herein is not significantly impaired. As the optional components, one type alone or two or more types in appropriate combination may be used from among conventionally known components used in general conductive compositions, etc., as necessary. Examples of the optional components include dispersants, thickeners, surfactants, defoamers, plasticizers, stabilizers, antioxidants, pH adjusters, preservatives, hardening accelerators, hardening retarders, organic binders, and (B) binding components other than addition-curing silicone rubber (e.g., various elastomers). Among them, it is preferable to include a dispersant. In addition, the conductive composition may contain (A) conductive powder other than electrolytic silver powder (e.g., simple noble metals such as platinum (Pt), gold (Au), and palladium (Pd), simple base metals such as nickel (Ni), aluminum (Al), and copper (Cu), carbonaceous materials such as carbon black, and mixtures and alloys thereof, etc.) alone or in appropriate combination.
[0050] The dispersant is a component that suppresses the aggregation of (A) electrolytic silver powder and enhances the dispersion stability of the conductive composition. In this specification, the term "dispersant" refers to a general compound having amphiphilicity with a hydrophilic portion and an oleophilic portion, and includes surfactants, wetting dispersants, and emulsifiers. As the dispersant, one type may be used alone or two or more types may be used in appropriate combination from among conventionally known dispersants. Examples include carboxylic acid dispersants having a carboxyl group, phosphoric acid dispersants having a phosphonic acid group, sulfonic acid dispersants having a sulfonic acid group, and amine dispersants having an amino group. From the viewpoint of enhancing affinity with (B) addition curing type silicone rubber and / or (C) organic solvent, an acid value dispersant having an acid value is preferable.
[0051] When the conductive composition contains an optional component, the dispersant may be about 0.01 to 1 part by mass, for example, 0.1 to 0.5 parts by mass, when the electrolytic silver powder (A) is taken as 100 parts by mass, which can suitably suppress aggregation of the conductive powder satisfying the above ratio (Y / X).
[0052] When the conductive composition contains an optional component, the amount of the optional component is typically less than that of (A) electrolytic silver powder, (B) addition cure type silicone rubber, and (C) organic solvent. As an example, when the entire conductive composition is taken as 100 mass%, the mass ratio of the optional component (e.g., dispersant) may be approximately 5 mass% or less, typically 3 mass% or less, 2 mass% or less, 1 mass% or less, for example 0.5 mass% or less. In addition, when the entire (A) electrolytic silver powder, (B) addition cure type silicone rubber, and (D) other optional components are taken as 100 mass%, the total of (A) electrolytic silver powder and (B) addition cure type silicone rubber may be approximately 80 mass% or more, typically 90 mass% or more, 95 mass% or more, for example 98 mass% or more, 99 mass% or more, 99.5 mass% or more. By suppressing the amount of the optional component to the necessary minimum, at least one of the electrical conductivity and elasticity of the conductive film can be more suitably improved.
[0053] <Method of using the conductive composition> The conductive composition can be preferably used for forming wiring or conductive circuits, joining or mounting various electronic components, connecting circuits, bonding various components together, etc. In one use example, a substrate having elasticity is first prepared. However, the substrate does not have to have elasticity. Examples of the elastic substrate include substrates made of rubber or elastomer such as silicone rubber, urethane rubber, fluororubber, nitrile rubber, acrylic rubber, styrene rubber, chloroprene rubber, ethylene rubber, propylene rubber, ethylene propylene rubber, and natural rubber.
[0054] Next, the conductive composition is applied onto the substrate to a desired thickness (e.g., 0.01 to 10 mm, 0.1 to 1 μm). The conductive composition can be applied (typically coated) using, for example, screen printing, gravure printing, a bar coater, a doctor blade, a slit coater, a gravure coater, a dip coater, a spray coater, a dispenser, or the like.
[0055] Next, the conductive composition applied onto the substrate is dried. From the viewpoint of suppressing damage to the substrate, it is preferable to set the drying temperature sufficiently lower than the heat resistance temperature of the substrate. Also, from the viewpoint of promoting curing and improving work efficiency, drying by heating may be performed as appropriate. When a substrate with low heat resistance is used, the upper limit of the heating temperature is about 200°C or less, preferably 150°C or less, and more preferably 100°C or less. Also, the drying time is typically about 1 hour to several days (for example, about 1 to 5 days). As a result, a conductive film is formed on the substrate. Also, components with boiling points lower than the above heating temperature, such as (C) organic solvent and (D) other optional components, can be vaporized and removed from the conductive film.
[0056] FIG. 1 is a cross-sectional view of a wiring board 10. The wiring board as used herein includes a circuit board, a printed circuit board, and the like. The wiring board 10 includes a substrate 12 and a conductive film 14 formed on the substrate 12 (for example, on the surface). The conductive film 14 is composed of a dried body of the conductive composition disclosed herein. The conductive film 14 is formed in a predetermined circuit pattern on the substrate 12 according to a predetermined design drawing. The conductive film 14 may be provided on only one side of the substrate 12 as shown in FIG. 1, or may be provided on both sides of the substrate 12. The conductive film 14 may be provided on only a part of the substrate 12, or may be provided over the entire surface of the substrate 12.
[0057] Conductive film 14 is mainly composed of (A) electrolytic silver powder and (B) addition-curing silicone rubber. When the entire solid content of conductive film 14 is taken as 100 volume %, the total of (A) electrolytic silver powder and (B) addition-curing silicone rubber is generally 80 volume % or more, typically 90 volume % or more, 95 volume % or more, for example 98 volume % or more, 99 volume % or more, 99.5 volume % or more, and may be substantially 100 volume %.
[0058] Considering a practical level, the initial volume resistivity of the conductive film 14 is preferably about 5 Ω·cm or less, for example 2 Ω·cm or less, preferably 1 Ω·cm or less, 0.5 Ω·cm or less, or even 0.2 Ω·cm or less. Furthermore, when the wiring board 10 is stretched in the length direction to twice its original length (200%) and then returned to its original length (100%), the rate of increase in the volume resistivity of the conductive film 14 is preferably about 100% or less, for example 50% or less, preferably 10% or less, or even 5% or less.
[0059] <Applications of conductive compositions> The conductive composition disclosed herein has excellent electrical conductivity and elasticity, and can therefore be suitably used in biomimetic driving materials such as artificial muscles and actuators, actuators and sensors for various electronic devices (e.g., pressure sensors, impact sensors, vibration sensors, etc.), body-worn wearable devices, robot devices, power assist devices, power generation devices, shock absorbing materials, vibration damping materials, etc.
[0060] Several embodiments of the present invention will be described below, but it is not intended that the present invention be limited to those embodiments.
[0061] [Preparation of conductive composition] First, the silver powder shown in Tables 1 to 4, an addition-curing silicone rubber, an organic solvent, and a dispersant were prepared.
[0062] [Table 1]
[0063] [Table 2]
[0064] [Table 3]
[0065] [Table 4]
[0066] Next, the prepared silver powder, silicone rubber, organic solvent, and dispersant were mixed in the masses shown in Tables 5 and 6 for each example, and uniformly stirred using a vacuum-equipped stirring / degassing device (Mazerustar KK-VT300, manufactured by Kurabo Industries, Ltd.). In this way, conductive compositions (Examples 1 to 15) were prepared. In addition to the mass, Tables 5 and 6 also show the volume ratio Y of the silver powder, the packing rate X, and the ratio (Y / X). The volume of the silver powder was calculated by multiplying the mass by the true density (10.5 g / cm 3 ) was calculated.
[0067] [Preparation of test pieces] Next, the conductive composition was applied to the surface of a silicon nitride substrate (size: length 35 mm × width 35 mm × thickness 0.32 mm) by screen printing using a metal mask (opening size: 10 mm × 10 mm, thickness: 0.12 mm). Next, the silicon nitride substrate with the conductive composition was heated and dried for 1 hour on a hot plate at 100°C. This caused the silicone rubber to harden and form a conductive film on the silicon nitride substrate, thereby producing a test specimen for each example (hereinafter also referred to as "test specimen 1"). In addition, in the same manner as in the case of test piece 1, a conductive film was formed on a silicone rubber substrate (size: length 40 mm × width 40 mm × thickness 1 mm, hardness: 30 degrees) to prepare a test piece for each example (hereinafter also referred to as "test piece 2").
[0068] [Evaluation of test specimens] The test pieces prepared above were evaluated in the following items (1) to (5). The evaluation results are shown in the corresponding columns of Tables 5 and 6, respectively. (1) Film curing "◯": A conductive film was formed, and the conductive film was not deformed or sticky when touched. "X": A conductive film could not be formed, and the conductive film was deformed or sticky when touched.
[0069] (2) Volume resistivity and electrical conductivity The volume resistivity of the conductive film of the test piece 1 was measured by a four-probe method using a resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., model: Loresta GP MCP-T610). Note that "OL" indicates that the upper limit of measurement was exceeded, and "-" indicates that the measurement was not yet performed. The conductivity is represented by the following symbols. "○": The volume resistivity was 1 Ω·cm or less. "X": Volume resistivity exceeded 1 Ω·cm.
[0070] (3)Stretchability The test piece 2 was attached to a tensile tester and stretched laterally to twice its length (200%), and then returned to its original length (100%). The state of the conductive film after stretching was visually confirmed. The volume resistivity was measured before and after stretching in the same manner as in (2) above, and the increase rate of the volume resistivity was calculated from the following formula: {(volume resistivity after stretching-volume resistivity before stretching) / volume resistivity before stretching}×100. The elasticity is represented by the following symbols. Note that "-" indicates that it was not measured. "◯": No cracks were generated in the conductive film after stretching, and the increase in volume resistivity after stretching was 10% or less. "X": Cracks occurred in the conductive film after stretching, or the increase in volume resistivity after stretching exceeded 10%.
[0071] (4) Possibility of reusing the conductive composition The conductive compositions of Examples 1 to 15 were examined for their reusability. Specifically, in the preparation of the test pieces in (1) above, after printing was performed using the conductive composition of each Example, it was confirmed whether the remaining conductive composition could be collected and reused. The reusability is indicated by the following symbols. Note that "-" indicates that the measurement was not performed. "◯": The conductive composition was not hardened and was in a state where it could be reused for printing.
[0072] (5) Overall evaluation "Good": Electrical conductivity, elasticity (and reusability) were both "good". "X": The electrical conductivity and / or elasticity were "X".
[0073] [Table 5]
[0074] [Table 6]
[0075] In Example 1, in which the ratio (Y / X) is greater than 4.0, and in Examples 5 and 6, in which the ratio (Y / X) is less than 1.5, the overall evaluation was "x". In detail, in Example 1, although the electrical conductivity of the conductive film was obtained, it could not withstand stretching to twice the length (200%), and the conductive network was broken, so that the elasticity standard was not met. In addition, in Examples 5 and 6, the volume resistivity was over the range, and it was not even possible to obtain electrical conductivity. And in Examples 9 and 10, in which dendritic silver was used, although the ratio (Y / X) satisfies the range of 1.5 to 4.0, the elasticity and electrical conductivity items were each "x", so the overall evaluation was "x".
[0076] In contrast to these examples (i.e., Examples 1, 5, 6, 9, and 10), Examples 2 to 4, 7, 8, and 11 to 15, which use dendritic electrolytic silver and have the above ratio (Y / X) of 1.5 or more and 4.0 or less, were found to have a volume resistivity of 1 Ω·cm or less and an elasticity of 200%, satisfying the standards for electrical conductivity and elasticity. It was also confirmed that these could be reused. These results support the technical significance of the invention disclosed herein.
[0077] Although it is not particularly limited, the present inventor believes that one of the reasons why a conductive film having both conductivity and elasticity can be formed by satisfying the above ratio (Y / X) is as follows. That is, the above filling rate X and the above volume ratio Y are both the volume ratio of electrolytic silver powder. In order to obtain sufficient elasticity, it is necessary to ensure the volume ratio of the addition curing type silicone rubber in the solid components (the total of electrolytic silver powder and addition curing type silicone rubber) in the conductive film. For this purpose, it is necessary to suppress the filling rate X of the electrolytic silver powder. If the above volume ratio Y is large relative to the above filling rate X, there will be an excess of electrolytic silver powder in the conductive film, and it can be assumed that although electrical conductivity is possible, the film strength is insufficient and it cannot withstand stretching. Conversely, if the above volume ratio Y is small relative to the above filling rate X, the volume ratio of the electrolytic silver powder will be small, and it can be assumed that electrical conductivity itself will be difficult. Therefore, it can be considered that it is necessary to balance the above ratio (Y / X) in order to form a conductive film having both electrical conductivity and elasticity.
[0078] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]
[0079] 10 Wiring board 12 Substrate 14 Conductive film
Claims
1. A conductive composition comprising electrolytic silver powder and an addition-curing silicone rubber, The tap density (g / cm 3 ) is the true density (g / cm 3 ) and multiplying the result by 100 to obtain the packing rate of the electrolytic silver powder, which is X (volume percent); When the ratio of the volume of the electrolytic silver powder to the total volume of the electrolytic silver powder and the silicone rubber is Y (volume %), the following formula is satisfied: 1.5≦(Y / X)≦4.0 The conductive composition satisfies the above.
2. The conductive composition according to claim 1 , wherein the volume ratio (Y) of the electrolytic silver powder is 10% by volume or more and 40% by volume or less.
3. The electrolytic silver powder has a tap density of 1.5 g / cm 3 3. The conductive composition according to claim 1 or 2, wherein:
4. The conductive composition according to any one of claims 1 to 3, wherein the filling rate (X) of the electrolytic silver powder is 5 volume% or more and 15 volume% or less.
5. The conductive composition according to claim 1 , which contains an organic solvent and is prepared in a paste form.
6. The organic solvent has a solubility parameter (SP value) of 6 (cal / cm 3 ) 0.5 Above 8 (cal / cm 3 ) 0.5 6. The conductive composition of claim 5, comprising the following compound:
7. A substrate; A conductive film formed on the substrate and made of a dried conductive composition according to any one of claims 1 to 6; A complex equipped with.
8. The composite according to claim 7 , wherein the conductive film has a volume resistivity of 1 Ω·cm or less.
9. 9. The composite according to claim 7, wherein when the composite is stretched to twice its length and then returned to its original length, the increase in volume resistivity of the conductive film is 10% or less.
Citation Information
Patent Citations
Conductive adhesive
JP2004197030A
Conductive paste and stretchable wiring board
JP2019110093A
Electroconductive composition, conductor, and flexible printed wiring board
WO2017026420A1
Electrically conductive composition
WO2017217509A1
